The challenges and impact of microvascular injury in ST-elevation myocardial infarction. (2nd April 2016) - Reinstadler, Sebastian Johannes; Stiermaier, Thomas; Fuernau, Georg; de Waha, Suzanne; Desch, Steffen; Metzler, Bernhard; Thiele, Holger; Eitel, Ingo
ABSTRACT: Despite successful restoration of epicardial coronary blood flow, a significant proportion of patients with ST-elevation myocardial infarction suffer from an impairment of the microvascular perfusion – a phenomenon termed no-reflow or microvascular injury (MVI). The underlying pathophysiology is complex and likely multifactorial. It is well established that MVI is associated with worse clinical outcome. Although MVI can be detected during coronary intervention and the post-infarction period, its prevention and treatment strategies remain a major challenge since most results of clinical studies have been disappointing so far. This review provides an overview on the main pathophysiological mechanisms of MVI and its diagnostic approaches. Moreover, it will discuss its clinical consequences and current strategies of prevention and treatment.